A spectroscopic study of the impact of arsenic speciation on arsenic/phosphorous uptake and plant growth in tumbleweed (Salsola kali) - de la Rosa, Guadalupe (2006)
This manuscript reports the toxic effects of As(2)O(3) (arsenic trioxide) and As(2)O(5) (arsenic pentoxide) on S. kali, as well as the arsenic and phosphate uptake, and arsenic coordination within plant tissues. Plants were germinated and grown for 15 days on a Hoagland modified medium containing either As(III) (arsenic trioxide) or As(V) (arsenic pentoxide). Subsequently, the seedlings were measured and analyzed using ICP-OES and XAS techniques. Plants stressed with 2 mg L(−1) of whichever As(III) or As(V) concentrated 245 ± 19, 30 ± 1, and 60 ± 3 mg As kg(−1) d. wt, or 70 ± 6, 10 ± 0.3, and 27 ± 3 mg As kg(−1) d. wt in roots, stems, and leaves, respectively. Arsenate was less toxic and more As translocation occurred from the roots to the leaves. All treatments reduced P concentration at root level; however, only As(V) at 2 and 4 mg L(−1) reduced P concentration at leaf level. Regardless the arsenic species supplied to the plants, arsenic was found in plant tissues as As(III) coordinated to three sulfur ligands with an interatomic distance of approximately 2.25 Å.